Characterisation of dispersions within annealed HVOLF thermally sprayed AlSnCu coatings - Kong, Chang-Jing; Moldovan, Grigore; Fay, Mike W.; McCartney, D. Graham; Brown, Paul D. (Institute of Physics Publishing, 2004)
High velocity oxy-liquid fuel (HVOLF) AlSnCu coatings are characterised following annealing for up to 5 hours at 300°C. A combination of statistical analysis of BSE images and TEM observations demonstrate the decrease in the number of sub-micron and nanoscale Sn particles with annealing, commensurate with a decrease in the coating microhardness. TEM evidence further suggests the coarsening of nanoscale Sn through a mechanism of a liquid phase migration within the Al matrix. EELS and EFTEM additionally allow the identification of the precipitation of theta'.